1989
DOI: 10.1016/0014-5793(89)80115-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transfer of the pigment bacteriorhodopsin into the eukaryote Schizosaccharomyces pombe

Abstract: The gene encoding for bacterio-opsin (bop gene) from Halobacterium halobium has been introduced in a yeast expression vector. After transformation in Schizosaccharomyces pombe, bacterio-opsin (BO) is expressed and was detected by antisera. The precursor protein of BO (pre-BO) is processed by cleavage of amino acids at the N-terminal end as in H. halobium. Addition of the chromophore, retinal, to the culture medium results in a slight purple colour of the yeast cells indicating the in vivo regeneration of BO to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Although functional expression in S. pombe was already dcmonstrated a few years ago [15,22] it was still surprising that tl~ archaebacterial protein bacteriorhodopsin could be expl essed in an amphibian cell. It was additionally satisfying from tl-e electrophysiological investigations that the direction of light in :luced current flow was always positive, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although functional expression in S. pombe was already dcmonstrated a few years ago [15,22] it was still surprising that tl~ archaebacterial protein bacteriorhodopsin could be expl essed in an amphibian cell. It was additionally satisfying from tl-e electrophysiological investigations that the direction of light in :luced current flow was always positive, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid pGEMHE contains the 3' and 5' untranslated regions of the b globin gene from Xenopus [14]. A promoter-free bop gene, encoding bacterioopsin including its signal sequence, was isolated from pBSbop [15] by cleavage with BamHI and HindIII and ligated into pGEMHE, behind the T7 RNA-polymerase promoter. E. coli was transformed by the RbCI method [16].…”
Section: Preparation Of Plasmid Dna and Mrna Synthesismentioning
confidence: 99%
“…Sitespecific mutants of bacteriorhodopsin were able to reproduce this behavior (16), showing that the ion specificity can be designed. Functional bacteriorhodopsin has also been transfected into naturally nonphotoactive organisms (17,18), introducing the possibility of producing specialized organisms that are optimized for solar energy conversion.…”
Section: Biological Energy Productionmentioning
confidence: 99%
“…In previous papers, it was shown that the fission yeast Schizosaccharomyces pombe is the only heterologous organism suitable for functional expression of bacteriorhodopsin (bR) in high yield (8,9), without isolation and reconstitution of the protein in artificial membranes as is necessary for the Escherichia coli expression system (3). The retinal protein bR expressed in S. pombe with its original leader sequence is located in the cell membrane as in the natural host Halobacterium salinarium.…”
mentioning
confidence: 99%
“…The retinal protein bR expressed in S. pombe with its original leader sequence is located in the cell membrane as in the natural host Halobacterium salinarium. To obtain functional bR in the fission yeast, bacterioopsin (bO) is regenerated in vivo by the addition of retinal to the culture medium (8,9).…”
mentioning
confidence: 99%